Application and perspective of CRISPR/Cas9 genome editing technology in human diseases modeling and gene therapy - Zhang, Man-Ling; Li, Hong-Bin; Jin, Yong (Frontiers in Genetics, 2024)
The Clustered Regularly Interspaced Short Palindromic Repeat (CRISPR) mediated Cas9 nuclease system has been extensively used for genome editing and gene modification in eukaryotic cells. CRISPR/Cas9 technology holds great potential for various applications, including the correction of genetic defects or mutations within the human genome. The application of CRISPR/Cas9 genome editing system in human disease research is anticipated to solve a multitude of intricate molecular biology challenges encountered in life science research. Here, we review the fundamental principles underlying CRISPR/Cas9 technology and its recent application in neurodegenerative diseases, cardiovascular diseases, autoimmune related diseases, and cancer, focusing on the disease modeling and gene therapy potential of CRISPR/Cas9 in these diseases. Finally, we provide an overview of the limitations and future prospects associated with employing CRISPR/Cas9 technology for diseases study and treatment.